2017
DOI: 10.1055/s-0043-115905
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of PEGylated Iron Oxide-Gold Nanoparticles for Delivery of Sulforaphane and Curcumin

Abstract: Natural products have been used for the treatment of various diseases such as cancer. Curcumin (CUR) and sulforaphane (SF) have anti-cancer effects, but their application is restricted because of their low water solubility and poor oral bioavailability. To improve the bioavailability and solubility of SF and CUR, we performed an advanced delivery of SF and CUR with PEGylated gold coated FeO magnetic nanoparticles (PEGylated FeO@Au NPs) to endorse SF and CUR maintenance as an effective and promising antitumor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…However, low bioavailability of phytochemicals is a major challenge. To overcome this, liposomal and other nanoformulations are being currently used to enhance their solubility in water and thus their bioavailability [ 148 , 149 , 150 , 151 ]. As phytochemicals are derived from natural sources, they are generally considered to be safe.…”
Section: Discussionmentioning
confidence: 99%
“…However, low bioavailability of phytochemicals is a major challenge. To overcome this, liposomal and other nanoformulations are being currently used to enhance their solubility in water and thus their bioavailability [ 148 , 149 , 150 , 151 ]. As phytochemicals are derived from natural sources, they are generally considered to be safe.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of curcumin in human subjects is limited due to its undesirable pharmacokinetic properties although; some clinical trials have unequivocally demonstrated the safety and efficacy of turmeric in human subjects (Gupta et al, ). Scientists are trying to improve the pharmacokinetic properties of curcumin for translating its wide range of activities into clinical benefits, e.g., formulation and applications of nanocurcumin (Danafar, ; Danafar, Sharafi, Askarlou, & Manjili, ; Kheiri Manjili et al, ; Nosrati, Sefidi, Sharafi, Danafar, & Manjili, ). Nanoparticles are a novel drug delivery mode on account of its high bioavailability in aqueous media, controlled drug release property, and higher physical stability and drug loading (Shaikh, Ankola, Beniwal, Singh, & Kumar, ; Yadav, Lomash, Samim, & Flora, ).…”
Section: Discussionmentioning
confidence: 99%
“…2017;Danafar, Sharafi, Askarlou, & Manjili, 2017;Kheiri Manjili et al, 2017;Nosrati, Sefidi, Sharafi, Danafar, & Manjili, 2018). Nanoparticles are a novel drug delivery mode on account of its high bioavailability in aqueous media, controlled drug release property, and higher physical stability and drug loading(Shaikh, Ankola, Beniwal, Singh, & Kumar, 2009;Yadav, Lomash, Samim, & Flora, 2012).…”
mentioning
confidence: 99%
“…In recent years, porous materials, such as mesoporous silica nanoparticles (MSNs), metal-organic frameworks 89 and iron oxide-gold nanoparticles 90 have been widely used in drug delivery. Kresge et al first used surfactants as structure directing agents to prepare highly ordered MSNs with uniform pore sizes in 1992.…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 99%